Wicked : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2009)
The stalker's identity has finally been revealed, but Spencer, Emily, Hanna and Aria are bound to repeat the past, and continue to be bad.
Keywords: Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Secrecy -- Juvenile Fiction; Conduct of life -- Juvenile fiction; Mystery fiction